PETROGENESIS STUDY OF THE OPHIOLITE COMPLEX OF THE TAPUNOPAKA AREA, NORTH KONAWE, SOUTHEAST SULAWESI - Akbar, Khalifa
The Ophiolite complex is an interesting formation to discuss. This is because the ultramafic rocks that are part of the Ophiolite complex are nickel laterite host rocks. However, apart from its economic aspect, the study of petrogenesis in the Ophiolite complex is important because it is related to the history of rock formation in the area. This study was conducted in the Tapunopaka area, North Konawe Regency, Southeast Sulawesi Province which is part of East Sulawesi Ophiolite (ESO), with the object of study of the Ophiolite complex rocks in the Tapunopaka area. Previous research conducted in ESO such as in the Kabaena, Soroako, Kolonodale, Boba, Ampana, Pagimana-Bunta, Poh Bay, Balantak, Lamasi Complex and Molawe-Andowia areas showed the Mid Oceanic Ridge (MOR), Oceanic Plateu, and Suprasubduction Zone (SSZ) ophiolite types. These results are the reason why it is important to study the petrogenesis of ofiolites in some of the Ofiolite Complexes in other areas included in the ESO that have not been studied such as the Tapunopaka area. This aims as additional data so that it can refine the genesis of the ESO in general. This study is to identify the characteristics and genesis of the rocks of the Ophiolite complex of the Tapunopaka area and to determine the series and type of ophiolite. To achieve these objectives, this study was conducted by field observation, and laboratory analysis which includes petrographic analysis and XRF analysis. Petrographic analysis was conducted to identify mineral composition, texture, structure, and mineral paragenesis. This is done to know how the rock was formed and the characteristics of the rock so that the ophiolite series can be known. And the XRF analysis is used to identify the main elements of the rock so that it can be used to identify the type of ophiolite in the study area. The results obtained are the rock characteristics of the Ophiolite complex of the study area which is composed of harzburgit, dunit, orthopyroxenite lens, and leuko- gabronorite pegmatite which cuts dunit and harzburgit. The rocks are found to have been altered with weak (1-25%) - moderate (26-50%) intensity. This alteration is shown by the presence of serpentine and iddingsite that partially alter olivin iv minerals, and the presence of talc and bastite that partially alter enstatit minerals. The genesis of the rocks of the ophiolite complex of the Tapunopaka area is that the dunit, harzburgit, orthopyroxenite rocks found in the study area are part of the upper mantle formed during a long cooling process. This is shown by the formation of textures such as poikilitic, consertal intergrowth, and cumulate textures. While the lamela exsolution texture is formed during slow cooling of crystals in a plutonic environment. The cumulate texture will form a layered structure that can still be found in several locations in the form of outcrops and boulders. The leuko- gabronorite pegmatite rocks that cut the harzburgite and dunite rocks are caused by the partial melting of upper mantle rocks that occurred during the spreading of the ocean floor. Based on the alteration minerals found, the rocks were altered by hydrothermal solutions with temperatures of 100°C-600°C during the expansion of the ocean floor. Based on the rocks found in the study area which are only harzburgite, dunite, orthopyroxenite, and gabbro but without other ophiolite rocks such as diabase dike and basalt, the ofiolite series of the Tapunopaka area is categorised as a fragmentary ophiolite series. Based on the geochemical analysis of harzburgit rocks identified as abyssal peridotite which is an ultramafic rock of MOR, as well as the results of the analysis of leuko-gabronorite rocks that show the affinity of toelitic magma, it can be concluded that the Ophiolite complex of the Tapunopaka area was formed in the Mid Oceanic Ridge (MOR) tectonic setting. The Tapunopaka Ophiolite complex has been displaced from its original location in the MOR environment to be exposed to the surface due to the impact between the Sundaland Microcontinent and the ESO and the Banggai-Sula Microcontinent which collided with the ESO later. This resulted in the ultramafic, which previously had a horizontal layer structure, becoming tilted as it is now.